Simplified Iohexol-Based Method for Measurement of Glomerular Filtration Rate in Goats and Pigs - Maaike K. van Gelder; Jasper Stevens; Tobias T. Pieters; Koen R. D. Vaessen; Jaap A. Joles; Marianne C. Verhaar; Karin G. F. Gerritsen (Biology, 2021)
The preclinical evaluation of novel therapies for chronic kidney disease requires a simple method for the assessment of kidney function in a uremic large animal model. An intravenous bolus of iohexol was administered to goats (13 measurements in n = 3 goats) and pigs (23 measurements in n = 5 pigs) before and after induction of kidney failure, followed by frequent blood sampling up to 1440 min. Plasma clearance (CL) was estimated by a nonlinear mixed-effects model (CLNLME) and by a one-compartmental pharmacokinetic disposition model using iohexol plasma concentrations during the terminal elimination phase (CL1CMT). A simple method (CLSM) for the calculation of plasma clearance was developed based on the most appropriate relationship between CLNLME and CL1CMT. CLSM and CLNLME showed good agreement (CLNLME/CLSM ratio: 1.00 ± 0.07; bias: 0.03 ± 1.64 mL/min; precision CLSM and CLNLME: 80.9% and 80.7%, respectively; the percentage of CLSM estimates falling within ±30% (P30) or ±10% (P10) of CLNLME: 53% and 12%, respectively). For mGFRNLME vs. mGFRSM, bias was −0.25 ± 2.24 and precision was 49.2% and 53.6%, respectively, P30 and P10 for mGFR based on CLSM were 71% and 24%, respectively. A simple method for measurement of GFR in healthy and uremic goats and pigs was successfully developed, which eliminates the need for continuous infusion of an exogenous marker, urine collection and frequent blood sampling.